Financial Perspectiveof Managinga Broiler Poultry Industry - Ms. Sabbineni Poojitha, Dr. K. Anusha, Dr. Venkateswara Rao Podile (International Journal of Advanced Science and Technology, 2020)
Poultry farming plays a crucial role in the rural economy of our country as it generates employment opportunities for the rural masses. It is a rapidly growing industry in the world and in India it is growing at an annual rate of 12-15 percent. The sustained growth of poultry industry has encouraged many farmers to adopt poultry farming as the main source of their income. In spite of various developments in this industry there are certain problems affecting its successful functioning. The study carried out intending to find out the financial aspects of poultry farming which was carried out by collecting data from 600 poultry farmers in Andhra Pradesh district. The data collected was analysed by using SPSS and the tests used for analysing data are moderation analysis.